A general and scalable approach to produce nanoporous alloy nanowires with rugged ligaments for enhanced electrocatalysis. Issue 26 (15th June 2018) - Qiu, H.-J.; Gao, J. J.; Chiang, F.-K.; Wen, Y. R.; Yao, A. Y.; Du, P.; Fang, G.; Wang, J. Q.; Liu, X. J.
Abstract : A general one-step dealloying approach is developed to produce nanoporous alloy nanowires with rugged ligaments and high-density defect sites. Abstract : Nanoporous metal nanowires with large surface areas, and a high density of defect sites play an important role in catalysis. Here, a general and scalable one-step dealloying strategy is developed to prepare nanoporous alloy nanowires with controllable compositions by manipulating the grain size, structure and composition of bulk Cu-based precursor alloys. We prepared PtCuAu nanoporous nanowires with a diameter of 200–500 nm and tunable composition by dealloying a diluted Pt1 Au0.5 Cu98.5 single-phase alloy with nanoscale column-like-structured grains. Material characterization suggests that the formation of separated nanowires is due to the large-scale shrinkage of the column-structured grains during dealloying of Cu, which also generates ultrafine nanopores and rugged alloy ligaments with a high density of defect sites in the nanowires. When used as a cathodic catalyst for the oxygen reduction reaction (ORR), the PtCuAu nanoporous nanowires exhibit a composition-dependent catalytic performance. The 8.0 M HNO3 dealloyed sample exhibits a specific activity of 4.12 mA cm −2 at 0.9 V, which is more than 14 times that of commercial Pt/C. With the advantages of being easy to scale up, highly reproducible and controllable, the fabrication strategy holds great promise to prepare nanocatalysts for fuel cells.